Dose-dependent effect of Scolymus hispanicus L. (sevketibostan) on ethylene glycol-induced kidney stone disease in rats - COŞKUN, ALİ; ERTAŞ, BÜŞRA; ELÇİOĞLU, HURİYE NURSEL (My University, 2022)
Kidney stone, also known as calcium oxalate nephrolithiasis, is one of the most common diseases worldwide. Calculi usually forms when urine becomes supersaturated with particular calcium salts such as calcium oxalate. In the present study, we investigated the ameliorative potential of the root extract of the Common golden thistle, Scolymus hispanicus L. (SH) on rats with ethylene glycol (EG) induced kidney stone disease. Sprague-Dawley rats, each weighing 250-300 g, were divided into three groups (n=6 per group): (i) Control (C); (ii) EG; and (iii) EG+SH. To induce nephrolithiasis, the rats received 1% of EG with drinking water, while the C group received normal drinking water during the study. SH extract 2 g/kg was added to the treatment from the 4th week onwards in EG+SH group. At the end of each experiment, rats were decapacitated and serum levels of calcium, magnesium, phosphorus, creatinine, aspartate aminotransferase (AST), alanine aminotransferase (ALT) and alkaline phosphatase (ALP) were assessed in all groups at 0, 4, and 8 weeks. Oxalic acid and creatininelevels were measured in urine samples collected at 24 h in metabolic cages. Renal tissues were evaluated histopathologically at the end of the experiment. After 8 weeks, serum creatinine levels were found decreased in the SH group while increased in the EG group. Serum magnesium and AST levels were also found decreased in the EG group, however, SH treatment reversed these values. The SH treatment also increased urinary oxalic acid levels. When the kidney tissue of EG group was examined, there was a high level of crystal/stone, especially in the renal cortex. In kidney tissues of the SH group, only small amounts of crystal/stone were observed. Our experimental findings have demonstrated the ameliorative potential of the aqueous extracts of S. hispanicus roots and shells on EG-induced in the kidney stones in rats. Isolation of active compounds of SH would be desirable to understand the biochemical mechanism behind the process better.
Keywords: Tıp; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Sağlık Bilimleri; Temel Tıp Bilimleri; Biyofizik; Biyokimya; Temel Bilimler; Medicine; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Health Sciences; Fundamental Medical Sciences; Biophysics; Biochemistry; Natural Sciences; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; Yaşam Bilimleri (LIFE); BİYOFİZİK; Biyoloji ve Biyokimya; BIOCHEMISTRY & MOLECULAR BIOLOGY; MOLECULAR BIOLOGY & GENETICS; Life Sciences (LIFE); BIOPHYSICS; BIOLOGY & BIOCHEMISTRY; İlaç Keşfi; Biyokimya (tıbbi); Yapısal Biyoloji; Moleküler Biyoloji; Klinik Biyokimya; Kanser Araştırmaları; Yaşlanma; Biyokimya, Genetik ve Moleküler Biyoloji (çeşitli); Genel Biyokimya, Genetik ve Moleküler Biyoloji; Drug Discovery; Biochemistry (medical); Structural Biology; Molecular Biology; Clinical Biochemistry; Cancer Research; Aging; Biochemistry, Genetics and Molecular Biology (miscellaneous); General Biochemistry, Genetics and Molecular Biology; Calcium oxalate; Common golden thistle; Crystal stone formation; Kidney tissue; Nephrolithiasis; Spanish oyster thistle; HYPEROXALURIA; ANTIOXIDANT; INJURY; Calcium oxalate; Common golden thistle; Crystal stone formation; Kidney tissue; Nephrolithiasis; Spanish oyster thistle